Comparison of social-ecological resilience between two grassland management patterns driven by grassland land contract policy in the Maqu, Qinghai-Tibetan Plateau. (May 2018) - Cao, Jianjun; Li, Mengtian; Deo, Ravinesh C.; Adamowski, Jan F.; Cerdà, Artemi; Feng, Qi; Liu, Minxia; Zhang, Jian; Zhu, Guofeng; Zhang, Xuebin; Xu, Xueyun; Yang, Shurong; et al.
Abstract: Embraced for decision-making, resilience has evolved as a meaningful term in areas such as ecology, the economy and society. After a policy of grassland contracts was implemented on the Qinghai-Tibetan Plateau, two grassland management patterns evolved: the multi-household management pattern (MMP) and the single-household management pattern (SMP). Within a resilience-driven perspective, this study compared the outcomes of these grassland management patterns by measuring their effects on the resilience of grazing, ecological, economic and social systems. Resilience indicators for each of the four systems were: grazing system (grazing space, transhumance, water source and reproduction); ecological system (vegetation including cover, biomass, species richness and soil properties including pH, organic carbon, total nitrogen and total phosphorus); economic system (income, expenditure and infrastructure) and the social system (health, assistance, social relations, cultural inheritance and institutional arrangements). In order to provide a social-ecological resilience framework for the two grassland management patterns, a decision support tool was applied to approximately gauge the resilience of each indicator. The results showed that each of the four systems under the MMP had a greater degree of resilience than the SMP, and that the overall resilience of the MMP was estimated at 5.8 units compared to about −5.8 units for the SMP. The relative success of the MMP was seen to rest largely on the maintenance of traditional management practices, social networks, trust and the low cost and high efficiency of informal institutions, which acted to reduce the risk of unsustainable development of ecological and social systems. The important take-home lesson from this study is that contracting of grasslands to private entities on the Qinghai-Tibetan Plateau, and in the rest of the world where similar land management practices exist, must be undertaken with caution.